Summary of CCAC hosted West African Virtual Workshop: Advancing Climate Action in Agriculture and Food Systems - Climate and Clean Air Coalition; CGIAR Research Program on Climate Change, Agriculture and Food Security; Food and Agriculture Organization of the United Nations; Oxfam; Stockholm Environment Institute; Government of Nigeria; Government of Côte d'Ivoire; Miami Ohio University; Global Research Alliance on Agricultural Greenhouse Gases; Government of Senegal; Sustainable Rice Platform; John Davison Associates (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
The Climate and Clean Air Coalition (CCAC) hosted a virtual workshop on Advancing Climate Action in Agriculture and Food Systems facilitated by the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS). This workshop had as objective to raise awareness on what can be done to advance climate action in agriculture and food systems in West Africa by sharing: recommendations from a World Resources Institute and Oxfam paper commission by the Coalition, particularly on Nationally Determined Contribution (NDC) enhancement; country experiences (Nigeria, Ivory Coast and Senegal), and other actions to support countries in the region.